Reformulasi Kebijakan Izin Trayek dan Izin Jalan bagi Angkutan untuk Mewujudkan Transportasi Berkelanjutan - Togatorop, Jein Lusiana; Budhiartie, Arrie; Ruswandi, Melia Rizkika (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Route permit and road permit policies in coal transportation constitute an important part of transportation governance and sustainable development in Indonesia. Sustainable development emphasizes a balance between economic, social, environmental, as well as legal and governance aspects, as reflected in Article 33 paragraph (4) of the 1945 Constitution. In practice, coal transportation management still faces various challenges, such as environmental pollution, road infrastructure damage, and weak supervision and compliance with licensing regulations. This study aims to analyze the legal basis, government supervision, and the role of licensing policies in achieving sustainable transportation. The method used is a normative juridical approach by examining laws and regulations, including Law Number 22 of 2009 on Road Traffic and Transportation, Presidential Regulation Number 95 of 2018 on Electronic-Based Government Systems, and Government Regulation Number 96 of 2021. The results show that route permits function as an instrument for controlling transportation operations; however, their implementation still faces internal and external obstacles, such as limited supervision and low public participation. Furthermore, the application of digital technology through electronic-based government systems and participatory approaches in policymaking can enhance the effectiveness of supervision and policy legitimacy. Therefore, strengthening regulations, improving supervision, and integrating sustainable development principles in coal transportation management are necessary to create a safe, efficient, and environmentally friendly transportation system.